The hidden thread: Russia and South Africa in the Soviet era (Irina Filatova and Apollon Davidson) (The Strategic Review for Southern Africa, 2020)
This is an important book that weaves together diverse strands of South African and Russian history, focusing on the ideological era in which Russia became a pivotal and global political player. The vast historical account begins in the pre-colonial era and cuts through some of the big themes in history, including among others the AngloBoer War, the revolutionary triumph of the Bolsheviks, the two world wars and the fall of apartheid